Bridging the Knowledge-Behavior Gap: How Islamic Financial Behavior Mediates the Relationship between Financial Literacy and Financial Wellbeing (Journal of Asian Development Studies, 2026)
This study examines the impact of Islamic Financial Literacy (IFLIT), Personality Traits (PST), and Islamic Financial Behaviours (IFB) on Financial Wellbeing (FWB). Drawing on the Theory of Planned Behaviour (TPB), the study examines the mechanisms by which individual characteristics shape financial outcomes. Primary data were collected through both online and offline media, and analysed using Structural Equation Modelling (SEM). The results demonstrate that IFLIT alone does not directly impact FWB. Moreover, IFLIT showed a significant but negative relationship with IFB, indicating a pronounced knowledge-behaviour gap. In contrast, IFB showed positive and significant results with FWB. Mediation results reveal that IFLIT indirectly influences FWB through IFB, whereas PST does not predict FWB behavioural mediation. Practically, the findings suggest that policymakers and Islamic Financial Institutions design nation-wide literacy programs focused on transitioning theoretical knowledge into behavioural action.